Exploring Realized Volatility through High-Frequency Data: The Role of Liquidity, Transaction Costs, and Influencing Factors. - Rinda Siaga Pangestuti; Isti Pujihastuti; Asty Khairi Inayah Syahwani (Politeknik Negeri Jakarta, 2025)
This research, which falls within the area of microstructure of financial markets, aims to compare liquidity with transaction costs, and determine the factors affecting volatility in small and large total asset energy companies in Indonesia. The use of data on companies with contrasting total assets contributes to providing investment portfolio management considerations for investors. The data used is taken from high-frequency stock price data per 30 minutes from Bloomberg subscribed. The illiquidity measurement method uses Amihud's Illiquidity, transaction costs use relative Bid-Ask Spread (BAS), and realized volatility is calculated using the square root of the realized variance. The use of 30-minute high-frequency stock price data can provide more detailed information. As a result, companies with small assets tend to have much greater stock price volatility, transaction costs, and illiquidity compared to companies with large assets. The factor affecting realized volatility is the volume of stock transactions. The greater the volume of stock transactions, the greater the volatility of stock prices. Keywords: High-Frequency Data; Realized Volatility; Amihud’s Illiquidity; Relative Bid-Ask Spread (BAS).